2013
DOI: 10.1007/s40279-013-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

The Pain of Tendinopathy: Physiological or Pathophysiological?

Abstract: Tendon pain remains an enigma. Many clinical features are consistent with tissue disruption-the pain is localised, persistent and specifically associated with tendon loading, whereas others are not-investigations do not always match symptoms and painless tendons can be catastrophically degenerated. As such, the question 'what causes a tendon to be painful?' remains unanswered. Without a proper understanding of the mechanism behind tendon pain, it is no surprise that treatments are often ineffective. Tendon pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
172
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(179 citation statements)
references
References 178 publications
5
172
0
2
Order By: Relevance
“…Neovascular ingrowth following collagen disorganization is proposed to be locally responsible for tendon-related pain. 44 On the contrary, Rio et al 45 have proposed a more centrally mediated response with multiple potential contributors to pain.…”
Section: Pain In Tendinopathymentioning
confidence: 99%
“…Neovascular ingrowth following collagen disorganization is proposed to be locally responsible for tendon-related pain. 44 On the contrary, Rio et al 45 have proposed a more centrally mediated response with multiple potential contributors to pain.…”
Section: Pain In Tendinopathymentioning
confidence: 99%
“…Tendinopathy may be defined as the, "...clinical syndrome of pain and dysfunction in a tendon..., " [20] and AT is likely an overuse injury [21,22]. The main symptom is pain upon palpation and loading, but the etiology of AT pain remains elusive [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Tendinopathy may be defined as the, "...clinical syndrome of pain and dysfunction in a tendon..., " [20] and AT is likely an overuse injury [21,22]. The main symptom is pain upon palpation and loading, but the etiology of AT pain remains elusive [20,22,23]. Studies have shown the development of bilateral Achilles changes in unilateral tendinopathy [24,25] and improvements on the contralateral side with unilateral Achilles surgery for those with bilateral AT [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations